Yellowish-orange and red emitting quinoline-based iridium(III) complexes: Synthesis, thermal, optical and electrochemical properties and OLED application - Altinolcek, Nuray; Battal, Ahmet; Tavasli, Mustafa; Cameron, Joseph; Peveler, William J.; Yu, Holly A.; Skabara, Peter J. (Elsevier Science Sa, 2020)
Two novel heteroleptic iridium(III) acetylacetonate (acac) complexes K3a and K3b were synthesised from cyclometallating ligands of 2-(4'-formylphenyl)quinoline lla and 2-(5'-formylphenyl)quinoline 11b. Complexes K3a and K3b were fully characterised by NMR spectroscopy, mass spectrometry and FT-IR. Differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA) indicate that both complexes were amorphous solids, stable up to 303 degrees C and 313 degrees C, respectively. Complexes K3a and K3b showed strong, high-energy absorption bands ( <400 nm) due to ligand-centred ((LC)-L-1) transitions and weaker, low-energy absorption bands (400 - 600 nm) arising from a mixture of metal-to-ligand charge transfer ((MLCT)-M-1/(MLCT)-M-3) and ligand-centred ((LC)-L-3) transitions. In degassed dichloromethane solutions, complexes K3a and K3b gave yellowish-orange and red phosphorescent emissions at 579 nm and 630 nm, with quantum efficiencies of 99.3 % and 79.3 %, respectively. At positive potential, complexes K3a and K3b exhibited a one-electron reversible oxidation (En) peak at 0.69 V and a quasi-reversible oxidation (ET1/2ox) peak at 0.60 V, respectively, which were assigned to the Ir (III)/Ir(IV) couple. At negative potentials, complexes K3a and K3b exhibited a one-electron irreversible reduction peak at -1.79 V and -1.94 V, respectively. Phosphorescent organic light-emitting diodes (PhOLEDs) were fabricated with a device configuration of ITO/PEDOT:PSS/EML/TPBi/LiF/Al, in which K3a and K3b gave yellowish-orange and red electroluminescence (EL) at 572 nm and 628 nm, respectively. Complex K3a gave the highest luminance of 2773 cd/m(2), current efficiency of 3.3 cd/A, external quantum efficiency of 1.2 % and maximum power efficiency of 1.05 lm/W with a turn-on voltage of 5.0 V (Device A).
Tavasli, Mustafa/0000-0002-9466-1111; BATTAL, AHMET/0000-0003-0208-1564; Cameron, Joseph/0000-0001-8622-8353
Keywords: Formyl group; 2-Phenylquinoline; Iridium; Heteroleptic; Phosphorescence; Electroluminescence